2021
DOI: 10.1101/2021.03.15.435179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A signature of Neanderthal introgression on molecular mechanisms of environmental responses

Abstract: Ancient human migrations led to the settlement of population groups in varied environmental contexts worldwide. The extent to which adaptation to local environments has shaped human genetic diversity is a longstanding question in human evolution. Recent studies have suggested that introgression of archaic alleles in the genome of modern humans may have contributed to adaptation to environmental pressures such as pathogen exposure. Functional genomic studies have demonstrated that variation in gene expression a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Finally, MPRAs have been used to understand the functional consequences of archaic admixture. Jagoda and colleagues [82] as well as Findley and colleagues [83] quantified the regulatory activity of variants introgressed from Neanderthals into the modern human gene pool. Both studies found that the in vitro activity of many of these variants was suggestive of causal effects on gene regulation.…”
Section: Current Applications Of Mprasmentioning
confidence: 99%
“…Finally, MPRAs have been used to understand the functional consequences of archaic admixture. Jagoda and colleagues [82] as well as Findley and colleagues [83] quantified the regulatory activity of variants introgressed from Neanderthals into the modern human gene pool. Both studies found that the in vitro activity of many of these variants was suggestive of causal effects on gene regulation.…”
Section: Current Applications Of Mprasmentioning
confidence: 99%
“…It remains challenging to computationally reconstruct regulatory mechanisms and therefore fully reconstruct the regulatory role of Neandertal DNA through its interaction with TFs. However, the results of our study and other previous work that investigated the impact of Neandertal DNA on the modification of TF binding motif sequences [59,60] have demonstrated the importance of studying the interaction of Neandertal DNA and TF activity in the quest to complete the picture of the impact of Neandertal introgression on the transcriptomic landscape of people today.…”
Section: Discussionmentioning
confidence: 57%